TNF-α-Producing Cryptococcus neoformans Exerts Protective Effects on Host Defenses in Murine Pulmonary Cryptococcosis - Fa, Zhenzong; Xu, Jintao; Yi, Jiu; Sang, Junjun; Pan, Weihua; Xie, Qun; Yang, Runping; Fang, Wei; Liao, Wanqing; Olszewski, Michal A. (Frontiers in Immunology, 2019)
Tumor necrosis factor alpha (TNF-α) plays a critical role in the control of cryptococcal infection, and its insufficiency promotes cryptococcal persistence. To explore the therapeutic potential of TNF-α supplementation as a booster of host anti-cryptococcal responses, we engineered a C. neoformans strain expressing murine TNF-α. Using a murine model of pulmonary cryptococcosis, we demonstrated that TNF-α-producing C. neoformans strain enhances protective elements of host response including preferential T-cell accumulation and improved Th1/Th2 cytokine balance, diminished pulmonary eosinophilia and alternative activation of lung macrophages at the adaptive phase of infection compared to wild type strain-infected mice. Furthermore, TNF- expression by C. neoformans enhanced the fungicidal activity of macrophages in vitro. Finally, mice infected with the TNF-α-producing C. neoformans strain showed improved fungal control and considerably prolonged survival compared to wild type strain-infected mice, but could not induce the sterilizing immunity. Taken together, our results support that TNF-α expression by an engineered C. neoformans strain while insufficient to drive complete immune protection, strongly enhanced protective responses during primary cryptococcal infection.